DATA MINING AND ITS EFFICACY IN KNOWLEDGE MANAGEMENT WITH RESPECT TO HRIS APPLICATION - Chopra, Tripti; David, Shine (International Journal of Research -GRANTHAALAYAH, 2016)
Industries are constantly trying to stay competitive by retaining its reputation in the market in which it is operating. Due to Globalization companies have to rethink their strategies and practices. A company’s strategy highly depends upon the use of application and the utilization of resources. Amidst all these HR factors tend to play a potential role in determining the effectiveness and competitiveness of an organization. HRIS is generally considered as managing people practices using IT enabled services. Thus it is a task of HRIS to cater to the needs of knowledge management .Knowledge management involves the practices which are utilized to get the right people at right time to train them and finally appraising their performance and reward them. This helps in keeping employees satisfied and happy. When the performance of an employee is evaluated a number of techniques are used to mine the utmost knowledge out of them. This is how HRIS is connected to Knowledge management. This empirical study is an effort in knowing the efficacy of data mining techniques in knowledge management and application of HRIS. The major focus of study is to know about the data base of employees for predicting the performance of employees and adopt a knowledge management strategy and the efficacy of data mining in doing so.